Behavior change interventions to promote adoption of e-bike shared mobility in a rural area: evidence from a mixed-method field trial - Wilson, Mark; Whitmarsh, Lorraine (Frontiers in Psychology, 2025)
Encouraging a shift to sustainable travel modes is essential for achieving net zero goals. This mixed-method study investigates the adoption of e-bike shared mobility in a rural context. Partnering with Cornwall Council and the shared e-bike provider Beryl, the study trialed two behavior change interventions to encourage people to use active modes; 151 residents and 14 Council staff took part. The two interventions were: (1) free Beryl bike credits, so people gain experience of using the e-bike share scheme on a trial basis, and (2) the ‘Pen portraits’ visioning tool, which uses evidence-based narratives to motivate people to consider how they could reduce car use in their daily lives. The effectiveness of the interventions was assessed over a four-week period through comparison to a control condition. During the study, uptake of e-bike share increased from 7 to 31% for residents, and from 29 to 71% for Council staff. Commuting and leisure or exercise were the most common journey purposes, although the bikes were also used as a component of multimodal travel. Beryl bikes encouraged mode shift for short journeys (1–2 miles), with 28% of e-bike share journeys substituting private car use, resulting in estimated carbon emission savings of 96–626 g CO2 per journey. Relative to the control group, more people in each of the three intervention groups used a Beryl bike (Control group = 21% of residents used Beryl, compared to: the visioning tool = 31%; Beryl bike credits = 37%; and Beryl bike credits plus the visioning tool = 36%). However, these differences are not statistically significant. Participants reported strong agreement that e-bike share provides a range of practical benefits such as reduced concern about bike maintenance and theft, as well as co-benefits such as providing exercise and improving mental health. The article concludes with a discussion of the practical and analytical challenges for conducting behavior change interventions in real-world settings. These findings are relevant for local authorities who are interested in tools and behavioral approaches for engaging with the public on low-carbon travel.